STRATEGI KEBAHASAAN DALAM PROGRAM BIMBINGAN REMAJA USIA SEKOLAH (BRUS) UNTUK MEMBENTUK SIKAP REMAJA TERHADAP HUBUNGAN PRANIKAH - ernawati ernawati; Intan Rahmawati; Dhiah Al Uyun (Aksara, 2026)
This study is motivated by the increasing phenomenon of premarital relationships among adolescents and the limited number of studies that position language as a primary factor in shaping attitudes. This study aims to describe the linguistic strategies employed in the School-Age Youth Guidance Program (BRUS) in shaping adolescents’ attitudes toward premarital relationships. This study uses a descriptive qualitative approach with frameworks from pragmatics, Systemic Functional Linguistics, and Critical Discourse Analysis. The data consist of facilitator utterances, participant responses, and BRUS module texts, which are collected through observation, documentation, and transcription, and then analyzed through data reduction, coding, and thematic interpretation. The results of this study indicate that the linguistic strategies in BRUS are dominated by directive speech acts, the use of modality such as must, should, have the right to, and can, as well as evaluative and preventive diction such as self control, risk, and responsibility. The results of this study also show that language in BRUS is not neutral, but functions to direct, legitimize, and reframe premarital relationships as risky behavior that should be avoided. In addition, adolescent responses demonstrate the internalization of values through expressions of understanding, assertiveness, caution, and future orientation. The implications of this study confirm that linguistic strategies play a strategic role in shaping adolescents’ attitudes persuasively without generating resistance, thus BRUS can be understood as an effective linguistic practice in constructing values and guiding adolescents’ decision making.